The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5897/ajbm2017.8345
|View full text |Cite
|
Sign up to set email alerts
|

Influence of entrepreneurship education, technology and globalisation on performance of SMEs in Nigeria

Abstract: Dwindling oil revenue, high youth unemployment, very high foreign exchange rates and recession are the challenges that Nigeria is currently faced with. There is therefore the urgent need for diversification and resuscitation of the economy. Small and medium enterprises (SMEs) are thus an important tool to achieve this. How therefore can acquisition of entrepreneurship education skills; adoption and use of technology; and globalisation through improved cross-border transactions enhance performance of SMEs, brin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The result affirms the study of Mitchelmore and Rowley (2010); Mohammed and Obeleagu-Nzelibe (2014) that strategically inclined entrepreneurs have the prerequisite skills to ensure the profitability of the firm and enhance the performance of an organization. The findings of this study is also consistent with the findings of Yusuf (2017) which confirmed that strategic entrepreneurship dimensions positively boosted profitability of SMEs. Similarly, Bosire and Nzaramba (2015) concurred that imbedding strategic entrepreneurship components in an organization leads to better business practices, augmented revenues and profits and ensure improvement in the overall performance of the firm.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…The result affirms the study of Mitchelmore and Rowley (2010); Mohammed and Obeleagu-Nzelibe (2014) that strategically inclined entrepreneurs have the prerequisite skills to ensure the profitability of the firm and enhance the performance of an organization. The findings of this study is also consistent with the findings of Yusuf (2017) which confirmed that strategic entrepreneurship dimensions positively boosted profitability of SMEs. Similarly, Bosire and Nzaramba (2015) concurred that imbedding strategic entrepreneurship components in an organization leads to better business practices, augmented revenues and profits and ensure improvement in the overall performance of the firm.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…The neo-Austrian theory (Kirzner, 1973) which is an extension of Austrian theory of entrepreneurship is part of the economic perspective of viewing entrepreneurship in consonance with the empirical findings from previous studies (Noordeh, 2010;Yusuf, 2017). Neo-Austrian theory is also known as Kirzner alertness theory of entrepreneurship.…”
Section: Adaptabilitymentioning
confidence: 83%
See 1 more Smart Citation
“…This would enhance necessary identification and avoidance of many pitfalls awaiting the less well trained and vigilant entrepreneurs. The training in entrepreneurial education may initially be perceived as a cost in terms of time and money but it would eventually be appreciated (Yusuf, 2017). Entrepreneurship education is designed to communicate and inculcate competencies, skills, knowledge, and values needed to recognize business opportunity, organize and start new business venture (Njenga & Theuri, 2016).…”
Section: Entrepreneurial Educationmentioning
confidence: 99%
“…Similarly, Daryani and Tabrizinia (2015) also confirmed that strategic entrepreneurship positively impact on competitive advantage and wealth-creation. This finding is consistent with the submission of other scholars that strategic entrepreneurship enhances firm's competitive advantage (Barchue & Aikaeli, 2013; Ireland & Webb, 2007; Ukenna et al, 2019).In the same vein, past studies have substantiated strategic entrepreneurship as the bedrock for achieving and improving on the competitive advantage of firms (Hoogendoorn, Zwan, & Thurik, 2017; Liyanage & Weerasinghe, 2018; Tur-Porcar, Roig-Tierno, & Mestre, 2018; Youssef, Boubaker, & Omri, 2017;Yusuf, 2017). Thus, it is affirmed that strategic entrepreneurship impulses firm to immediately act to sudden changes in the external business environment that might pose as threat to the attainment of the firms' objectives.…”
mentioning
confidence: 99%